Analysis of variants of solid fuel production from sugar industry waste and conditions needed for its burning - Shutyuk, Vitaliy; Vasylenko, Tatiana; Bessarab, Alexander; Samiilenko, Serhii (My University, 2015)
The use of alternative fuel and energy resources should be considered as the strategic approach to solving energy issues of Ukraine’s economy. Currently the potential capabilities of growing sugar beet in Ukraine are twice as good as the need for sugar production support. On a total mass basis the major part of solid waste of sugar industry (up to 75…83 % in relation to the mass of processed sugar beet) accrues to pulp. Currently the most of pulp is not used and has to be taken to stockpiles or fields before the start of the new sugar campaign. Potentially, the amount of pulp which can be used for energy needs takes up 4,5…5 million tons per year, or in conversion to dry basis - 330…370 thousand tons. There are two possible ways of its use: use of dried pulp as secondary fuel and direct firing of pressed pulp.
Keywords: sugar industry; pulp; biofuel; burning; цукрова промисловість; жом; біопаливо; спалювання; кафедра технології консервування; кафедра теплоенергетики та холодильної техніки; кафедра економіки праці та менеджменту